2019
DOI: 10.1097/md.0000000000014567
|View full text |Cite
|
Sign up to set email alerts
|

Single- versus 2-stage reconstruction for chronic post-radiation chest wall ulcer

Abstract: Radiation therapy can have adverse effects on normal tissue and cause chronic ulcers. The purpose of this study was to compare breast cancer patients who underwent single-stage reconstruction with patients who underwent 2-stage reconstruction for chronic radiation-induced necrotic ulcers of the chest wall. This retrospective study comprised of 50 patients with chronic radiation-induced chest wall ulcers who underwent chest wall reconstruction in our hospital between January 2002 and January 2016. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…poor condition [3,6]. This is because once ulceration occurs, it does not heal well, and necrotic tissue can spread much deeper and wider than what is visible.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…poor condition [3,6]. This is because once ulceration occurs, it does not heal well, and necrotic tissue can spread much deeper and wider than what is visible.…”
Section: Original Articlementioning
confidence: 99%
“…In some cases, radiation-induced ulceration develops over 10 years after radiation [2]. Because of the ulcers' unique pathophysiology including necrosis, atrophy, fibrosis, vascular damage, carcinogenesis, and impaired cellular repair potential, healing is usually delayed and some ulcerations become chronic [3].…”
Section: Introductionmentioning
confidence: 99%
“…We discussed the case with plastic surgeons and the infectious disease colleagues to anticipate potential intraoperative complications and mutually developed an adequate plan. We all decided not to implant synthetic materials for underlying infection and osteomyelitis (12), and therefore we unanimously considered auto-grafts the best tool for body repair in her case.…”
Section: Casementioning
confidence: 99%
“…The radiation dose, radiation time and patient’s condition are the risk factors known to affect its occurrence. It has been reported that radiation doses exceeding 70 Gy/7 wk/30 fractions are prone to cause such ulcers[ 1 ]. Radiation-induced ulcers of the chest wall are secondary, progressive and irreversible, with a duration of as short as several months and as long as years or decades.…”
Section: Introductionmentioning
confidence: 99%